1975
DOI: 10.1007/bf00231994
|View full text |Cite
|
Sign up to set email alerts
|

The major ganglion in the pelvic plexus of the male rat

Abstract: To further evaluate the role of autonomic ganglia in the regulation of pelvic visceral activity, the neural elements in the major pelvic ganglion of the male rat have been studied with histochemixal and electron microscopic techniques. The principal findings are that the ganglion is composed of cholinergic and adrenergic ganglion cells as well as small intensely fluorescent (SIF) cells. Polarity in the ganglion is indicated by clustering of small ganglion cells which stain intensely for acetylcholinesterase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2
4

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(52 citation statements)
references
References 30 publications
4
42
2
4
Order By: Relevance
“…The ratio of numbers of the two types of cells was different from cluster to cluster. This may be one of the reasons why the present findings were different from those of Dail et al (1975). Kitao et al (1981) reported that the ratio changed with growth.…”
Section: Major Pelvic Ganglioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The ratio of numbers of the two types of cells was different from cluster to cluster. This may be one of the reasons why the present findings were different from those of Dail et al (1975). Kitao et al (1981) reported that the ratio changed with growth.…”
Section: Major Pelvic Ganglioncontrasting
confidence: 71%
“…Bock (1982) assumed that the LG type cells (type II of Lu et al 1976) in the autonomic ganglion are endocrine in function, although the possibility could not be ruled out that the LG and the SG type cells act as interneurons, because they form many afferent and efferent synapses. On the contrary, Dail et al (1975) and Abe et al (1983) pointed out that the GC cells do not show any close relationship with blood capillaries here. Therefore, it is unlikely that the GC cells act as either endocrine or chemoreceptive cells.…”
Section: Synapsescontrasting
confidence: 63%
See 1 more Smart Citation
“…In most species, these numerous small ganglia locate close to the pelvic organs. As to the rat, functionally identical groups of neurons are clustered in two large major pelvic ganglia and a small adjacent clump of accessory ganglia (Dail et al 1975).…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated by continuing efforts -largely in the male rat -to describe the composition, distribution and function of the peripheral pelvic nerves. While consensus exists on major nerves such as the pelvic (Langworthy, 1965;Dail et al 1975;Hulsebosch & Cogeshall, 1982;Lucio et al 1994;Hubscher & Johnson, 2000), the pudendal (Larsson & Södersten, 1973;Hulsebosch & Cogeshall, 1982;McKenna & Nadelhaft, 1986Pacheco et al 1997), and the hypogastric (Langworthy, 1965;Hulsebosch & Cogeshall, 1982;Dail et al 1985Dail et al , 1989Claire & Bradley, 1998;Hubscher & Johnson, 1999, 2000, reports on the genitofemoral nerve (GFn) remain contradictory.…”
Section: Introductionmentioning
confidence: 99%